(untitled) - Cummings, Jack (Hoboken, N.J., 2006)
The Real Estate Investor's Guide to Cash Flow and Equity Management tackles the pros and cons of a major dilemma for investors: whether to concentrate on increasing equity or cash flow. In this reliable guide, Jack Cummings provides insider techniques and investment strategies for every situation, every time.
Keywords: Real estate investment,Đầu tư bất động sản